Co-Inhibitory Molecules – Their Role in Health and Autoimmunity; Highlighted by Immune Related Adverse Events - Greisen, Stinne R.; Aspari, Maithri; Deleuran, Bent (Frontiers in Immunology, 2022)
Immune checkpoint receptors are key players in regulating the immune response. They are responsible for both generating an immune response sufficient to kill invading pathogens, balancing the same response, and protecting against tissue destruction or the development of autoimmune events. The central role of the co-inhibitory receptors also referred to as inhibitory immune checkpoints, including PD-1 and CTLA-4 has become especially evident with the cancer treatments targeting these receptors. Blocking these pathways enhances the immune activity, resulting in both an increased chance of cancer clearance, at the same time induction of immune-related adverse events (irAE). Some of these irAE progress into actual autoimmune diseases with autoantibodies and symptoms, undistinguished from the naturally occurring diseases. This review will take advantage of the lessons learned from immune checkpoint blockade and relate this knowledge to our understanding of the same pathways in naturally occurring autoimmune diseases, mainly focusing on rheumatic diseases.